Disentangling the influence of salience and familiarity on infant word learning: methodological advances - Bortfeld, Heather; Shaw, Katie; Depowski, Nicole (Frontiers in Psychology, 2013)
The initial stages of language learning involve a critical interaction between infants' environmental experience and their developing brains. The past several decades of research have produced important behavioral evidence of the many factors influencing this process, both on the part of the child and on the part of the environment that the child is in. The application of neurophysiological techniques to the study of early development has been augmenting these findings at a rapid pace. While the result is an accrual of data bridging the gap between brain and behavior, much work remains to make the link between behavioral evidence of infants' emerging sensitivities and neurophysiological evidence of changes in how their brains process information. Here we review the background behavioral data on how salience and familiarity in the auditory signal shape initial language learning. We follow this with a summary of more recent evidence of changes in infants' brain activity in response to specific aspects of speech. Our goal is to examine language learning through the lens of brain/environment interactions, ultimately focusing on changes in cortical processing of speech across the first year of life. We will ground our examination of recent brain data in the two auditory features initially outlined: salience and familiarity. Our own and others' findings on the influence of these two features reveal that they are key parameters in infants' emerging recognition of structure in the speech signal. Importantly, the evidence we review makes the critical link between behavioral and brain data. We discuss the importance of future work that makes this bridge as a means of moving the study of language development solidly into the domain of brain science.